Advances in group processes. Vol. 28 - Thye, Shane R.; Lawler, Edward J. (Emerald, 2011)
Advances in Group Processes publishes theoretical analyses, reviews, and theory based empirical chapters on group phenomena. It is the only edited volume of its kind explicitly devoted to group related phenomena and brings together diverse papers on the subject from a wide range of fields. The series adopts a broad conception of 'group processes'. This includes work on groups ranging from the very small to the very large, and on classic and contemporary topics such as status, power, exchange, justice, influence, decision-making, intergroup relations and social networks. Volume 28, including contributions from Stanford University and Harvard Business School, examines topics such as: graded status characteristics and expectation states; standardizing open interaction coding for status processes; creating community through language among San Pedro Longshoremen; applying identity theory to moral acts of commission and omission; and joint commitments and social groups. It looks at key questions about the legitimacy of groups and the mobilization of resources, and also reducing social distance through the role of globalization in global public goods provision.
Keywords: Social groups.; Social interaction.; elektronické knihy; electronic books